(untitled) (West African Journal on Sustainable Development, 2024)
The consistent home vices and divorce without recurring decimal to what causes it in Enugu State, Nigeria necessitated the study. Therefore, the purpose of the study was to investigate the influence of university education on the holistic empowerment of female science students in Enugu State: Implications for sustainable development goals. Four research questions and four null hypotheses tested at .05 level of significance guided the study. A correlational research design was adopted for the study. Simple random sampling technique was used in selecting 172 female science education students comprising 119 single and 53 married from Department of Science Education. The instrument used for data collection were four in number: the holistic empowerment of university education scale, (HEUES), intellectual empowerment scale (IES), financial empowerment scale (FES), and socio-cultural empowerment scale (SCES) adapted from 21 items scale of Abhinanadan, Abhishek, Sanath and Gururaj (2023). The reliability of the instruments was tested using Cronbach’s alpha which yielded indices of 0.76, 0.85, 0.91 and 0.75 respectively. Data were analyzed using mean, standard deviation and path analysis to test the proposed hypotheses. The finding of the study amongst others indicated that university education intellectually, financially and socio-culturally influenced holistic empowerment of female science students irrespective of marital status in Enugu state. Based on the findings, it was recommended that government agencies and private individuals to roll out measures to encourage female folk to attain university education.